2011
DOI: 10.3791/2629
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Neural Basis of Adaptive Locomotor Behavior in Insects

Abstract: Studying the neural basis of walking behavior, one often faces the problem that it is hard to separate the neuronally produced stepping output from those leg movements that result from passive forces and interactions with other legs through the common contact with the substrate. If we want to understand, which part of a given movement is produced by nervous system motor output, kinematic analysis of stepping movements, therefore, needs to be complemented with electrophysiological recordings of motor activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…During the stance phase, movement of a middle leg on the inner side of the curve is directed toward the body of the animal, as if pulling the animal via flexion of the FTi-joint toward the side of the turn. In contrast, a middle leg on the outer side pushes backward along the length axis of the animal (Gruhn et al 2009(Gruhn et al , 2011. We studied whether the occurrence of reflex reversals differed in the two middle legs during optomotor stimulation, which induces turning in direction similar to walking in a curve (Gruhn et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the stance phase, movement of a middle leg on the inner side of the curve is directed toward the body of the animal, as if pulling the animal via flexion of the FTi-joint toward the side of the turn. In contrast, a middle leg on the outer side pushes backward along the length axis of the animal (Gruhn et al 2009(Gruhn et al , 2011. We studied whether the occurrence of reflex reversals differed in the two middle legs during optomotor stimulation, which induces turning in direction similar to walking in a curve (Gruhn et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…To elicit curve walking in the stick insects, the stripes on both screens moved to either the right or left, which elicited the respective walking direction ( Fig. 1; Gruhn et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Certain high-risk HLA haplotypes are shared between celiac disease and T1D patients (45). The German BABYDIET cohort was initiated to investigate whether delayed exposure to dietary gluten could delay development of b-cell autoantibodies (46). Although no protective effect was found, a longitudinal analysis of the gut microbiota of 22 autoantibody-positive and 22 autoantibody-negative BABYDIET study children revealed altered bacterial interaction networks at the ages of 6 and 24 mo (47).…”
Section: Human Studies Link Gut Microbiota Composition To T1d Riskmentioning
confidence: 99%
“…10. Switching from forward to backward walking in the experiment (A) [adapted from Gruhn et al (2011) with permission] and in the model (B). Traces are as indicated in A.…”
Section: Modeling Switches Between Forward and Backward Movementsmentioning
confidence: 99%